The efficacy of lapine preconditioned or genetically modified IL4 over-expressing bone marrow-derived mesenchymal stromal cells in corticosteroid-associated osteonecrosis of the femoral head in rabbits. (August 2021) - Maruyama, Masahiro; Moeinzadeh, Seyedsina; Guzman, Roberto Alfonso; Zhang, Ning; Storaci, Hunter W.; Utsunomiya, Takeshi; Lui, Elaine; Huang, Elijah Ejun; Rhee, Claire; Gao, Qi; Yao, Zhenyu; Takagi, Michiaki; et al.
Abstract: Cell-based therapy for augmentation of core decompression (CD) using mesenchymal stromal cells (MSCs) is a promising treatment for early stage osteonecrosis of the femoral head (ONFH). Recently, the therapeutic potential for immunomodulation of osteogenesis using preconditioned (with pro-inflammatory cytokines) MSCs (pMSCs), or by the timely resolution of inflammation using MSCs that over-express anti-inflammatory cytokines has been described. Here, pMSCs exposed to tumor necrosis factor-alpha and lipopolysaccharide for 3 days accelerated osteogenic differentiation in vitro . Furthermore, injection of pMSCs encapsulated with injectable hydrogels into the bone tunnel facilitated angiogenesis and osteogenesis in the femoral head in vivo, using rabbit bone marrow-derived MSCs and a model of corticosteroid-associated ONFH in rabbits. In contrast, in vitro and in vivo studies demonstrated that genetically-modified MSCs that over-express IL4 (IL4-MSCs), established by using a lentiviral vector carrying the rabbit IL4 gene under the cytomegalovirus promoter, accelerated proliferation of MSCs and decreased the percentage of empty lacunae in the femoral head. Therefore, adjunctive cell-based therapy of CD using pMSCs and IL4-MSCs may hold promise to heal osteonecrotic lesions in the early stage ONFH. These interventions must be applied in a temporally sensitive fashion, without interfering with the mandatory acute inflammatory phase of bone healing.